Pengaruh Kualitas Pelayanan Dan Kepuasan Pelanggan Terhadap Loyalitas Pelanggan Pada Euphoria Store - Hasri, Yulia Elista Indani; Rangga, Yoseph Darius Purnama; Lewar, Maria Viviana Nurak; Odang, Laura Maria Jeanne (Universitas Nusa Nipa Maumere, 2026)
This study aims to identify the level of customer loyalty and analyze the influence of service quality and customer satisfaction on customer loyalty at Euphoria Store. This research is motivated by the increasing competition in the cosmetics and skincare retail industry, which requires business owners to provide excellent service quality and create customer satisfaction in order to enhance customer loyalty. This study employed a quantitative approach using a survey method. The population consisted of Euphoria Store customers, with a sample of 100 respondents selected through purposive sampling. Data were collected through questionnaires and analyzed using multiple linear regression with the assistance of SPSS version 23. Hypothesis testing was conducted using the t-test, F-test, and coefficient of determination (R²). The results of the study indicate that service quality has a positive and significant effect on customer loyalty at Euphoria Store. Customer satisfaction also has a positive and significant effect on customer loyalty. Simultaneously, service quality and customer satisfaction have a positive and significant effect on customer loyalty at Euphoria Store. The coefficient of determination (R²) of 0.647 indicates that 64.7% of the variation in customer loyalty can be explained by service quality and customer satisfaction, while the remaining 35.3% is influenced by other factors outside the scope of this study. Based on the findings, it can be concluded that service quality and customer satisfaction are important factors in enhancing customer loyalty. Therefore, Euphoria Store should continuously improve its service quality, maintain product availability, and pay close attention to customer satisfaction in order to strengthen customer loyalty and achieve long-term business success.